The acceptance level of picture archiving and communication system amongst radiographers - Mazlyfarina Mohamad; Nur Syahidatul Asmaa Muhammad Rusdi; Sa'don Samian (Penerbit Universiti Kebangsaan Malaysia, 2015)
Picture archiving and communication system know as (PACS) is a rapidly growing technology in the healthcare industry in Malaysia and provides a positive development for patient services and one of the factors that influence the success of this system is the level of user acceptance. However, the acceptance level of the radiographers in using PACS and also the factors influencing its usage are unknown. Thus, this study seeks to determine the factors that influence the radiographers on the acceptance of PACS in their daily tasks. A study was conducted in three hospitals to determine the level of acceptance of radiographers in the implementation of PACS and factors influenced it. A questionnaire applying the theory of 'Technology Acceptance Model' which uses components of perceived of usefulness (PU) and perceived ease of use (PEU) to determine the acceptance level of radiographers to PACS was used to collect data. Quantitative approach is adopted with questionnaire has been distributed to 76 radiographers at Pusat Perubatan Universiti Kebangsaan Malaysia, Pusat Perubatan Universiti Malaya and Hospital Serdang. Result analysis of stepwise multiple regression found that PEU was found an important influencing factor in determining the acceptance level of radiographers (R2 = 0.077) where this construct has resulted in radiographers do not feel overburdened in completing their duties. This study reported that radiographers are more interested in completing their job on ease of use while usefulness of the PACS system was not a main influence. Therefore, it is important for organizations which want to implement PACS to create an overview about PACS to the radiographers. The training should be given before the execution of system to enable acknowledgement of the advantages offered by PACS.